Relationship between changes in thymic emigrants and cell-associated HIV-1 DNA in HIV-1-infected children initiating antiretroviral therapy. - De Rossi, A; Walker, A; De Forni, D; Klein, N; Gibb, D (2005)
OBJECTIVES AND METHODS: To investigate the relationship between cell-associated HIV-1 dynamics and recent thymic T-cell emigrants, HIV-1 DNA and T-cell receptor rearrangement excision circles (TREC, a marker of recent thymic emigrants) were measured in peripheral blood mononuclear cells in 181 samples from 33 HIV-1-infected children followed for 96 weeks after antiretroviral therapy (ART) initiation. RESULTS: At baseline, HIV-1 DNA was higher in children with higher TREC (P=0.02) and was not related to age, CD4 or HIV-1 RNA in multivariate analyses (P>0.3). Overall, TREC increased and HIV-1 DNA decreased significantly after ART initiation, with faster HIV-1 DNA declines in children with higher baseline TREC (P=0.009). The greatest decreases in HIV-1 DNA occurred in children with the smallest increases in TREC levels during ART (P=0.002). However, this inverse relationship between changes in HIV-1 DNA and TREC tended to vary according to the phase of HIV-1 RNA decline (P=0.13); for the same increase in TREC, HIV-1 DNA decline was much smaller during persistent or transient viraemia compared with stable HIV-1 RNA suppression. CONCLUSIONS: Overall, these findings indicate that TREC levels predict HIV-1 DNA response to ART and suggest that immune repopulation by thymic emigrants adversely affects HIV-1 DNA decline in the absence of persistent viral suppression, possibly by providing a cellular source for viral infection and replication.